Efficacy and safety of Tongxinluo capsules combined with conventional therapy for acute myocardial infarction: a systematic review and meta-analysis - Ouyang, Dan; Jiang, Xiao; Wang, Hui; Xu, Ma Li; Qi, Hang; Li, Xin Hui; Cao, Jian Zhong (Frontiers in Pharmacology, 2025)
BackgroundTongxinluo capsule, a formally classical commercial Chinese polyherbal preparation, has been utilized to treat patients with acute myocardial infarction for decades.Purpose:This meta-analysis aimed to comprehensively evaluate the clinical outcomes of tongxinluo capsule treated acute myocardial infarction.MethodsRandomized controlled trials evaluating the effectiveness of tongxinluo capsule alone or in combination with conventional therapy in patients with acute myocardial infarction were identified from eight major databases: Chinese Biomedical Medicine, China National Knowledge Infrastructure, Wanfang Med Database, China Science and Technology Journal Database, PubMed, and Cochrane Central Register of Controlled Trials. In addition, two clinical trial registry platforms (clinicalTrials.gov and the WHO International Clinical Trials) were also searched for relevant studies, with the search extending to all published literature until December 2024. The initial screening and evaluation of the studies were carried out by two independent reviewers who assessed each study according to predefined eligibility criteria. The risk of bias in the research was evaluated using the Cochrane Collaboration’s methodology for assessing methodology. Meta-analysis was carried out using RevMan 5.3 software, and publication bias was assessed utilizing StataMP 14.0. The evidence’s quality was determined by the Grading of Recommendations Assessment, Development, and Evaluation process.ResultsThis research included a total of 36 randomized controlled trials with 7002 patients. The meta-analysis revealed that Tongxinluo capsule combined with conventional treatment significantly decreased the 1-month MACCE rate (RR = 0.62, 95% CI 0.47 to 0.81; p = 0.0007), along with the individual risks of 1-month MACCE, including cardiac death (RR = 0.68, 95% CI 0.50 to 0.93; p = 0.02) and myocardial reinfarction (RR = 0.11, 95% CI 0.01 to 0.94; p = 0.04). After 12 months of treatment, the MACCE rate (RR = 0.61, 95% CI 0.49 to 0.75; p < 0.00001), cardiac death (RR = 0.69, 95% CI 0.50 to 0.96; p = 0.03), myocardial reinfarction (RR = 0.32, 95% CI 0.13 to 0.75; p = 0.009), and stroke (RR = 0.42, 95% CI 0.20 to 0.87; p = 0.02) were also reduced. The remaining secondary outcomes—1-month stroke (RR = 0.44, 95% CI 0.44 to 1.44; p = 0.18), 12-month (RR = 0.12, 95% CI 0.01 to 2.14; p = 0.15) emergent coronary revascularization, 12-month all-cause mortality (RR = 0.78, 95% CI 0.60 to 1.01; p = 0.06)—showed no differences. Furthermore, the combination of Tongxinluo capsule and conventional therapy increased the incidence of the adverse drug reaction, mainly gastrointestinal discomfort (RR = 1.80, 95% CI 1.14 to 2.84; p = 0.01). However, there were no differences in the liver function levels of aspartate transaminase (SMD = −0.24, 95% CI -0.54 to −0.07; p = 0.12) and alanine aminotransferase (SMD = −0.25, 95% CI -0.55 to 0.05; p = 0.11), or the kidney function levels of blood urea nitrogen (SMD = 0.32, 95% CI -0.21 to 0.86; p = 0.23) and creatinine (SMD = 0.10, 95% CI -0.20 to 0.40; p = 0.52).ConclusionCurrent data indicates that Tongxinluo capsule, used as an adjuvant treatment, may enhance clinical outcomes for AMI patients at 1- and 12-month. Moreover, it may enhance heart function, regulate lipid peroxidation, and suppress inflammatory levels.